2020
DOI: 10.1002/mde.3219
|View full text |Cite
|
Sign up to set email alerts
|

Does CEO compensation matter in boosting firm performance? Evidence from listed French firms

Abstract: The paper investigates the impact of chief executive officer (CEO) compensation on firm performance from a sample of 155 listed French companies on SBF 120, over 2009-2018. Findings suggest that an increase in CEO compensation seems to improve the accounting-based firm performance, nevertheless it hurts the firm stock market value. More pronounced results are reported when we control for sector compensation interactions. We argue that attractive compensation may improve the executive services in achieving shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
(84 reference statements)
3
5
0
Order By: Relevance
“…Firm size has negative and statistically significant effect on firm performance within the two models at a 5 percent level. The results are in line with those of prior studies [88,89]. Finally, the coefficients of firm age and R&D intensity are negative but not significant.…”
Section: Multivariate Regression Analysissupporting
confidence: 90%
“…Firm size has negative and statistically significant effect on firm performance within the two models at a 5 percent level. The results are in line with those of prior studies [88,89]. Finally, the coefficients of firm age and R&D intensity are negative but not significant.…”
Section: Multivariate Regression Analysissupporting
confidence: 90%
“…In the same vein, we examine the effect of contemporaneous as well as previous performance on executive pay in US companies. More recently, Zoghlami (2021) have used a sample of 155 listed French companies on SBF 120, in the period 2009-2018, and have showed that CEO compensation is positively linked to firm performance.…”
Section: The Firm Performance and Its Relationship With Executive Compensationmentioning
confidence: 99%
“…Although most research evidences show that executive compensation incentive can improve corporate performance, there are still many problems in the application of incentive executive compensation incentive. Zoghlami (2021) [20] found that increasing executive compensation seemed to improve company performance, but it damaged the stock market value of the company. The author believed that attractive compensation may improve the service of executives in achieving the goals of shareholders, but investors did not seem to like the increase of executive compensation.…”
Section: The Relationship Between Executive Compensation and Corporat...mentioning
confidence: 99%